2001
DOI: 10.4049/jimmunol.167.2.1053
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Delivery of Human and Viral IL-10 in Murine Sepsis

Abstract: Adenovirus (Ad) gene therapy has been proposed as a drug-delivery system for the targeted administration of protein-based therapies, including growth factors and biological response modifiers. However, inflammation associated with Ad transduction has raised concern about its safety and efficacy in acute inflammatory diseases. In the present report, intratracheal and i.v. administration of a first-generation adenoviral recombinant (E1,E3 deleted) either containing an empty cassette or expressing the anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
6
30
0
Order By: Relevance
“…11,12 In the present report, we confirmed that at a dose of 10 7 , survival after induction of zymosan lung injury with pre-treatment with buffer or various adenoviral vectors at 10 7 particles). As seen previously, 13 the effects of adenoviral recombinants expressing viral IL-10 were markedly better than those seen with human IL-10, although both treatments improved outcome significantly. In animals pretreated with adenovirus expressing viral IL-10, mortality 18 days after zymosan administration was less than 10%, whereas mortality was 50% for animals pretreated with adenovirus expressing human IL-10, and 100% for the vehicle-treated animals.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…11,12 In the present report, we confirmed that at a dose of 10 7 , survival after induction of zymosan lung injury with pre-treatment with buffer or various adenoviral vectors at 10 7 particles). As seen previously, 13 the effects of adenoviral recombinants expressing viral IL-10 were markedly better than those seen with human IL-10, although both treatments improved outcome significantly. In animals pretreated with adenovirus expressing viral IL-10, mortality 18 days after zymosan administration was less than 10%, whereas mortality was 50% for animals pretreated with adenovirus expressing human IL-10, and 100% for the vehicle-treated animals.…”
Section: Resultssupporting
confidence: 76%
“…[25][26][27] We previously reported that intratracheal instillation of low dose (10 7 p) adenoviral recombinants expressing IL-10 reduced the magnitude of the inflammatory response to zymosan, 13 and similar results were seen here (data not shown). Interestingly, pretreatment with 10 9 particles of human and viral IL-10 was associated with a significant increase in the magnitude of the inflammatory response, as determined by increased plasma concentrations of TNFa and IL-6 ( Figure 3).…”
Section: Il-10 Gene Therapy In Msof Pf Mcauliffe Et Alsupporting
confidence: 89%
See 3 more Smart Citations